The Urgency of Revising the Finance Services Authority Regulation Number 77/POJK.01/2016 As an Umbrella Law in Practicing Peer to Peer Lending Based on Financial Technology in Indonesia - Ubaidillah Kamal; Ayup Suran Ningsih (Pandecta Research Law Journal, 2021)
ABSTRACTThe presence of Peer to Peer Lending Based on Financial Technology (Fintech) in Indonesia is a real manifestation of a technological advancement. The advantage of technology is its simplicity, but like two sides of a coin, technological advances in financial services also cause polemics and problems. Based on complaints received by the Financial Services Authority, there are 2 things that are often complained about by borrower, it is regarding the unwise use of private data that is used as a way of collecting debt by peer to peer providers and the way they contact borrower for collecting debt. Even though it is considered controversial, the growth of fintech service providers has accelerated to 200%. These are show the urgency that the Financial Services Authority Regulation No.77/POJK.01/2016 requires revision because it is not in suitable with the current development of Fintech. The Financial Services Authority Regulation No.77/ POJK.01/2016 requires revisions regarding the restrictions on access on borrower’s device, it must be only camera, microphone, and location only, no access to contact or gallery, then related to more detailed in regulating the operations of the fintech provider company, and related regulation for the minimum capital for the fintech provider company.Keywords: Peer to Peer; Lending; Fintech; Borrower ABSTRAKHadirnya Peer to Peer Lending Berbasis Financial Technology (Fintech) di Indonesia adalah manifestasi nyata dari sebuah kemajuan teknologi. Keunggulan dari suatu teknologi adalah kemudahannya, namun ibarat 2 sisi mata uang, kemajuan teknologi dibidang jasa keuangan ini juga menimbulkan polemik serta permasalahannya. Berdasarkan pengaduan yang diterima Otoritas Jasa Keuangan terdapat 2 hal yang sering diadukan oleh peminjam, yaitu perihal penggunaan data pribadi peminjam secara tidak bijak dan cara penagihan hutang oleh perusahaan penyedia layanan yang dinilai tidak sesuai ketentuan yang berlaku. Walaupun dinilai kontroversial, namun pertumbuhan perusahaan penyedia layanan fintek melaju sangat pesat sampai 200%. Beberapa hal ini menunjukan urgensi bahwa peraturan otoritas jasa keuangan No.77/POJK.01/2016 memerlukan revisi karena sudah tidak sesuai dengan perkembangan Fintek sekarang ini. Peraturan Otoritas Jasa Keuangan No.77/POJK.01/2016 memerlukan revisi terkait pembatasan akses perusahaan penyedia layanan terhadap gawai dari peminjam, yaitu hanya kamera, mikrofon, dan lokasi saja, tidak ada akses ke kontak maupun galeri, selanjutnya terkait pengaturan yang lebih detail terhadap operasional perusahaan penyedia layanan, dan pengaturan terkait minimum modal bagi perusahaan penyedia layanan.Kata Kunci: peer to peer; lending; fintek; pinjaman